Correlation of soft palate length with velum obstruction and severity of obstructive sleep apnea syndrome. Issue 3 (June 2018) - Lim, Ju-Shin; Lee, Jae Woo; Han, Chun; Kwon, Jang-Woo
Abstract: Objective: Our aim in this study was to analyze whether soft palate length and velum obstruction during sleep are correlated and to determine the effects of related parameters on obstructive sleep apnea syndrome (OSAS) severity. We used computed tomography to measure soft palate length and drug-induced sleep endoscopy (DISE) to evaluate velum obstruction severity. Patients also underwent polysomnography (PSG) for evaluation of OSAS severity. Methods: A retrospective cohort of 67 patients with OSAS treated between May 1st, 2013 and July 31st, 2016 was analyzed. Each patient underwent DISE, PSG, and computed tomography. Using DISE, velum obstruction was categorized by the VOTE classification method. Using computed tomography, soft palate length was measured as the length of the posterior nasal spine to the uvula. Correlations of velum obstruction in DISE and PSG parameters (obstructive apnea, hypopnea, apnea hypopnea index (AHI), respiratory effort related arousal (RERA), respiratory disturbance index (RDI), baseline SaO2, and minimum SaO2 ) with soft palate length were also analyzed. Results: Among the 67 patients, the average PNS-U length was 39.90 ± 4.19 mm. Length was significantly different by age but not by other demographic characteristics such as sex, past history, or BMI. DISE revealed a statistically significant difference of velum obstruction degree; the cutoff value for PNS-U was 39.47 mm. The PSG results, obstructive apnea, AHI, RDI, baseline SaO2, and minimum SaO2 were correlated with PNS-U length, while other results such as hypopnea and RERA showed no correlation. Conclusion: Analysis of soft palate length showed that increased PNS-U length was associated with higher rates of obstructive apnea, AHI, and RDI as assessed by PSG. In contrast, lower baseline SaO2 and minimum SaO2 values were seen by PSG; more severe velum obstruction was seen by DISE. We propose that when a soft palate is suspected in OSAS, computed tomography measurement of soft palate length is a valid method for estimating the degree of velum obstruction and the severity of OSAS.